MINDiT: A framework for media independent access to things - Corujo, Daniel (2012)
Deploying smart environments often implies a plethora of co-existing devices and services, each with their own set of features, requirements and interfacing characteristics. These intricate scenarios are further exacerbated when such devices are coupled with networking capabilities, globalizing their interaction opportunities to create the so-called Internet of Things. In such interconnected heterogeneous environments, the joint operation of entities requires a flexible framework that enables and simplifies interfacing between elements. In this paper, we propose MINDiT, a framework that provides a common abstract interface towards the communication support with different entities. It incorporates cross-layer mechanisms inspired on the existing IEEE 802.21 technology, suitably modified to facilitate and optimize deployment in scenarios featuring both high-level, and low-powered network-restricted entities. MINDiT was validated through a prototype built over an open-source IEEE 802.21 implementation. We further compared its signaling impact against other solutions, and evaluated its performance over a smart environment featuring a multimedia scenario with multiple devices and services.